The Science of Architecture. Representations of Portuguese National Architecture in the 19th century World Exhibitions: archetypes, models and Images - Rodrigues, Paulo Simões (2013)
To show how in the second half of the 19th century, influenced by the positivist philosophy, the architectonic theory and culture established a determinisc connexion between the historic and territorial specificities of the nations and the formal singularities of the national architectures: a building was seen as a biological structure created by the specific social, moral and physical characteristics of a given environment. This connexion led to the recognition of the national architectonic archetypes in the monuments of the past and allowed to explain scientifically the formation of those archetypes. The world exhibitions were privileged displays for the affirmation and advertisement of these national architectonic archetypes. Portugal did it by sending photo albums and models of its more representative historic monuments to the major world exhibitions.